Transcriptomics and non-targeted metabolomics provide mechanistic insights into the improvement of the growth performance and meat quality of lambs supplemented with fermented Lycium barbarum residues - Jiale Liao; Wencan Ke; Bing Wang; Min Du; Qiang Lu; Yajun Zhang; Guijie Zhang (Animal Nutrition)
This study investigated the effects of Lycium barbarum residues (LBR) and fermented L. barbarum residues (FLBR) on the growth performance and meat quality of lambs. Eighteen lambs were randomly assigned into three groups and fed either a basal diet (CON) or the same diet supplemented with 5.0% LBR or FLBR for a period of 90 days. The underlying mechanisms responsible for the beneficial effect of LBR and FLBR on the longissimus thoracis (LT) and intramuscular fat (IMF) tissues of lambs were examined using multiomics techniques. Our findings showed that FLBR supplementation significantly enhanced the average daily gain, feed efficiency, and nutrient digestibility (P < 0.05 or P < 0.01). Serum total protein (P = 0.007) and glucose (P = 0.002) levels were higher in the FLBR-fed lambs, while urea nitrogen level was lower (P = 0.001). Additionally, the levels of rumen acetate (P = 0.002) and propionate (P = 0.011) were significantly elevated, while ammonia-nitrogen (NH3–N), isobutyrate and isovalerate decreased (P < 0.05 or P < 0.01) following FLBR supplementation. Post-mortem meat quality was also improved by FLBR, as evidenced by enhanced total antioxidant capacity, superoxide dismutase activity, pH, redness (a∗), tenderness and water holding capacity (P < 0.05 or P < 0.01), alongside a reduction in the malonaldehyde content (P < 0.001). Transcriptomic analysis identified 962 differentially expressed genes (DEGs, FLBR vs CON) and 782 DEGs (FLBR vs LBR) in LT, and 1313 DEGs (FLBR vs CON) and 1221 DEGs (FLBR vs LBR) in IMF. The ribosome signaling pathway related genes in LT tissue were activated by the FLBR diet (P < 0.05), showing a higher anabolism of protein. The genes involved in fatty acid biosynthesis in IMF tissue were upregulated by the FLBR diet (P < 0.05), showing a higher anabolism of lipids. Metabolomics analysis identified the 1732 differential metabolites in LT tissue following FLBR supplementation, with significant alterations in metabolites such as carnosine, L-arginine and L-proline, which may serve as potential biomarkers for meat quality betterment. In conclusion, FLBR supplementation might have modified anabolism of proteins and fatty acid, as well as muscle metabolomic profiles, leading to improvements in both growth performance and meat quality in fattening lambs.